Larval dispersal of Pocillopora damicornis at high latitude coral communities - Tioho, Hanny (Universitas Sam Ratulangi, 2013)
In order to elucidate the patterns of dispersal in scleractinian coral Pocillopora damicornis near the northern limit of its latitudinal range, a total of 50 colonies (15-25 cm in diameter) of this coral were collected from Ooshima Island, Japan, and transplanted within one hour to the area of Satsuki, where they were not present before. Three concentric areas were established such as; the parental area (PA), intermediate area (IA) and outer area (OA). A total of 831 new corals were found in 1997 while 54.3% of these occurred in PA, 30.5% in IA and 15.1% in OA. In 1998, 52.3% of recruits settled in PA, 30.5% in IA and 17.2% in OA. A significant difference in the density of recruits was found among three areas, but recruit density was not significantly different between years and there was no interaction between area and year. There was no significant difference in the number of recruits among different directions, indicating no tendency for larvae to be concentrated in one particular direction. The present study suggests that the planulae of P. damicornis have limited dispersal distances at high-latitudesÂ©Â Untuk menjelaskan pola penyebaran karang scleractinia Pocillopora damicornis yang berada di batas Utara penyebarannya, total 50 koloni (15-25 cm) dari karang ini dikumpulkan dari Pulau Ooshima, Jepang, dan di transplantasikan dalam waktu satu jam ke daerah Satsuki yang tidak ditemukan jenis ini. Tiga daerah ditetapkan yaitu, Daerah Induk (PA), Daerah Tengah (IA), dan Daerah Luar (OA). Sebanyak 831 karang baru ditemukan pada tahun 1997, sementara 54,3% ditemukan di PA, 30,5% di IA dan 15,1% di OA. Pada tahun 1998, 52,3% ditemukan di PA, 30,5% di IA, dan 17,2% di OA. Ditemukan perbedaan yang signifikan untuk kepadatan antara ketiga daerah tersebut, tetapi tidak ada perbedaan yang signifikan antar tahun dan tidak ada interaksi antara daerah dan tahun. Tidak ada perbedaan yang signifikan dalam jumlah pada arah yang berbeda sehingga hal ini menunjukkan tidak ada kecenderungan bagi larva untuk terkonsentrasi pada satu arah tertentu. Penelitian ini menunjukkan bahwa planula P.